Osteogenic Induction of Wharton’s Jelly-Derived Mesenchymal Stem Cell for Bone Regeneration: A Systematic Review - Ayu Suraya Ansari; Muhammad Dain Yazid; Nur Qisya Afifah Veronica Sainik; Rabiatul Adawiyah Razali; Aminuddin Bin Saim; Ruszymah Bt Hj Idrus (Stem Cells International)
Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) are emerging as a promising source for bone regeneration in the treatment of bone defects. Previous studies have reported the ability of WJ-MSCs to be induced into the osteogenic lineage. The purpose of this review was to systematically assess the potential of WJ-MSC differentiation into the osteogenic lineage. A comprehensive search was conducted in Medline via Ebscohost and Scopus, where relevant studies published between 1961 and 2018 were selected. The main inclusion criteria were that articles must be primary studies published in English evaluating osteogenic induction of WJ-MSCs. The literature search identified 92 related articles, but only 18 articles met the inclusion criteria. These include two animal studies, three articles containing both in vitro and in vivo assessments, and 13 articles on in vitro studies, all of which are discussed in this review. There were two types of osteogenic induction used in these studies, either chemical or physical. The studies demonstrate that WJ-MSCs are able to differentiate into osteogenic lineage and promote osteogenesis. In light of these observations, it is suggested that WJ-MSCs can be a potential source of stem cells for osteogenic induction, as an alternative to bone marrow-derived mesenchymal stem cells.